ORGANIZATION OF INDEPENDENT WORK OF STUDENTS IN TRAINING - Кокарєва, А. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
In Article rassmatryvaetsya problem samostoyatelnoy organization work with students uchetom Specificity s Professional training. Solution oboznachennыh problems sposobstvovat aktyvyzatsyy learning students in High society uchebnыh zavedenyyah